Prove that : \[\displaystyle x + 2^nx^2 + 3^nx^3 + 4^nx^4 + ...... = x\frac{d}{dx}x\frac{d}{dx}......(\textrm{n times})\frac{1}{1-x} \]

Note: \(|x| \in [0,1)\)

No vote yet

1 vote

×

Problem Loading...

Note Loading...

Set Loading...

Easy Math Editor

`*italics*`

or`_italics_`

italics`**bold**`

or`__bold__`

boldNote: you must add a full line of space before and after lists for them to show up correctlyparagraph 1

paragraph 2

`[example link](https://brilliant.org)`

`> This is a quote`

Remember to wrap math in \( ... \) or \[ ... \] to ensure proper formatting.`2 \times 3`

`2^{34}`

`a_{i-1}`

`\frac{2}{3}`

`\sqrt{2}`

`\sum_{i=1}^3`

`\sin \theta`

`\boxed{123}`

## Comments

Sort by:

TopNewestFor \(|x|\in [0,1)\), we have,

\[\frac 1{1-x}=1+x+x^2+\ldots=\sum_{k=0}^\infty x^k\]

Applying the operator \(x\frac{\textrm d}{\textrm dx}\), we have,

\[\frac 1{1-x}=1+x+x^2+\ldots=\sum_{k=0}^\infty x^k\implies x\frac{\textrm d}{\textrm dx}\frac 1{1-x}=\sum_{k=0}^\infty x\cdot kx^{k-1}=\sum_{k=0}k^1x^k\]

Repeating this argument \(n\) times, we have,

\[\left(x\frac{\textrm d}{\textrm dx}\right)^n\frac 1{1-x}=\sum_{k=0}k^nx^k=x+2^nx^2+3^nx^3+\ldots\]

Log in to reply